PENGARUH MOTIVASI INTRINSIK DAN MOTIVASI PROSOSIAL TERHADAP KEPEMIMPINAN TRANSFORMASIONAL - Aryaningrat, Gusti Ayu Peby Karmila; Satrya, I Gusti Bagus Honor (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.09.TAHUN.2024DO - 10.24843/EEB.2024.v13.i09.p03, 2024)
Human Resources (HR) in an organization plays an important role as a determinant of the organization's success in achieving its long-term goals. A leader's accuracy in choosing a leadership style that suits the job is very necessary in order to achieve organizational goals. The purpose of examine intrinsic motivation and prosocial motivation towards transformational leadership. This research was conducted at the Badung Regency Regional Government. Respondents in this study numbered 112 people, calculated as 70 percent of the total number of 161 Echelon III officials. The technique used in this research is multiple linear regression analysis. The results show that intrinsic motivation has a positive and significant effect on transformational leadership in Echelon III officials. Prosocial motivation has a positive and significant effect on transformational leadership in Echelon III officials. The theoretical implications of this research confirm the previously existing theory, namely Self-Determination Theory (SDT). This research uses Self-Determination Theory (SDT) as a theoretical basis in measuring the influence of intrinsic motivation and prosocial motivation on transformational leadership It is hoped that the practical implications of this research can provide Echelon III officials can treat employees individually who have different abilities, and knowledge.